The Role of Islamic Education Subject in Increasing Student’s Emotional Intelligence in SMAN 12 Bandarlampung - Hadiati, Eti; SY, Mukti (Universitas Islam Negeri Raden Intan Lampung, 2022)
Emotional intelligence is the ability to control emotions, maintain and boost motivation to not easily give up, control and cope with the stress, accept the reality, as well as be acceptance during difficulties. The emotional intelligence cannot be separated education, especially from Islamic Education subject. Thus, the research aimed to find the role of Islamic Education subject in improving students’ emotional intelligence and the factors that inhibit Islamic Education subject in improving students’ emotional intelligence at SMAN 12 Bandar Lampung. This research used qualitative research with descriptive approach. Data collection methods used focus group discussions (FGD), observation, interviews and documentation. The data were analyzed by data reduction, data presentation and conclusion drawing. From this study, it was concluded that Islamic Education subject at SMAN 12 Bandar Lampung improved the students’ emotional intelligence through religious activities such as reading the Qur'an, commemorating religious events, and visiting other students who were in difficulties. They were done in addition to the main activity of teaching and learning in the classroom. On the other hand, the obstacle factors consisted of internal and external factors, among others: IQ factor/ genetic intelligence that was student’s ability to learn the material which affected their ability to comprehend it, the lack of students’ concentration to participate in learning activities, and lack of attention from their parents that also affected students’ learning motivation.